Prognostic Biomarkers in COVID-19: The Impact of Neutrophil-Lymphocyte Ratio, Ferritin, Platelet-Lymphocyte Ratio, and D-Dimer - Sawitri, Endang; Kalalo, Lily Pertiwi; Ramadhan, Muhammad Aidil Aulia (Technium BioChemMed, 2026)
Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, was declared a global pandemic by the World Health Organization (WHO) in March 2020. This indicates that identifying factors associated with mortality in affected patients is essential for optimizing clinical management. Therefore, this study aims to analyze the differences in Neutrophil-Lymphocyte Ratio (NLR), ferritin, Platelet-Lymphocyte Ratio (PLR), and D-dimer levels between COVID-19 patients who recovered and those who did not, as well as identify the key prognostic factors. The study was conducted using a cross-sectional method at RSUD Abdoel Wahab Sjahranie, Indonesia, from January to December 2021. The sample population consisted of adult COVID-19 patients with complete data on neutrophil, lymphocyte, and platelet counts, as well as ferritin and D-dimer levels. Among the 682 patients, the average age was 53.43 years, where 66.9% recovered and 33.1% died. The results showed that there were significant differences in NLR, ferritin, and D-dimer levels between the recovered and deceased groups (p<0.05), with the deceased group having higher levels. Although PLR also showed a significant difference (p=0.017), it was not significant in the multivariate analysis (p= 0.896). The multivariate analysis identified NLR (OR=1.064), ferritin (OR=1.001), and D-dimer (OR=1.086) as significant predictors of mortality. In conclusion, NLR, ferritin, and D-dimer were effective in predicting COVID-19 mortality, while PLR was ineffective. These findings provide valuable insights for improving clinical management strategies for COVID-19 patients.